1999
DOI: 10.1071/ea98097
|View full text |Cite
|
Sign up to set email alerts
|

Mobility and persistence of three sulfonylurea herbicides in alkaline cropping soils of south-eastern Australia

Abstract: Biologically active residues of the herbicides metsulfuron-methyl, chlorsulfuron and triasulfuron were estimated with field pea bioassays in soil samples to 80 cm depth from 4 field trials in south-eastern Australia situated on neutral to highly alkaline soil. Residues were both mobile and persistent at low levels. Leaching occurred beyond the lowest sampling depth during the winter–spring growing season. Metsulfuron-methyl was the most mobile of the 3 herbicides. Plant-back experiments involving susceptible c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 0 publications
0
11
1
Order By: Relevance
“…The pre-emergent Group B SU herbicides have limited incorporation requirement compared with many other preemergent herbicides, making them eminently suitable for minimum-tillage systems. However, the intensity of SU herbicide use in alkaline soils has historically been influenced by lengthy plant-back periods limiting rotational options, with Group D herbicides a common alternative (Black et al 1999;Boutsalis et al 2006;Nufarm Australia 2018a). This has potentially resulted in the following: higher herbicide resistance in acidic soils due to reduced cultivation associated with Group B herbicide use; lower Group A resistance in alkaline soils because some weed control can be obtained by the cultivation needed for incorporation; and increased Group D resistance in the alkaline soils due to greater selection pressure (Boutsalis et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pre-emergent Group B SU herbicides have limited incorporation requirement compared with many other preemergent herbicides, making them eminently suitable for minimum-tillage systems. However, the intensity of SU herbicide use in alkaline soils has historically been influenced by lengthy plant-back periods limiting rotational options, with Group D herbicides a common alternative (Black et al 1999;Boutsalis et al 2006;Nufarm Australia 2018a). This has potentially resulted in the following: higher herbicide resistance in acidic soils due to reduced cultivation associated with Group B herbicide use; lower Group A resistance in alkaline soils because some weed control can be obtained by the cultivation needed for incorporation; and increased Group D resistance in the alkaline soils due to greater selection pressure (Boutsalis et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…imidazolinones) or alkaline (e.g. sulfonylureas), thereby limiting crop-rotation options (Black et al 1999;Kennedy 2003). Reduced tillage can result in increased soil acidity, enhancing the persistence of some herbicides or limiting crop rotations through the pH level itself (Blevins et al 1983;Locke and Bryson 1997).…”
Section: Introductionmentioning
confidence: 99%
“…1 Cinosulfuron tion, a very low animal toxicity has been reported (Tomlin 1994). However, depending on environmental conditions, sulfonylureas or their metabolites may persist excessively in the environment with a residual phytotoxicity (Anderson and Humburg 1987;Black et al 1999;Sarmah et al 1999). They can also reach the aquifer (Battaglin et al 2000).…”
Section: Introductionmentioning
confidence: 98%
“…In soils that are neutral to alkaline, they exist as anions and degrade very slowly (Sarmah et al 1998). Black et al (1999) and Hollaway et al (2006) found that most chlorsulfuron residue was located in the top 20 cm of soil. Studies in Queensland reported minimal carry-over of sulphonylureas in alkaline soils in a sub-tropical climate (Walker & Robinson 1996) and indicated that recropping was safe within 1 year of the application of chlorsulfuron (Osten & Walker 1998).…”
Section: Introductionmentioning
confidence: 99%